PHILOSOPHY AND CONCEPT OF KNOWLEDGE ACCORDING TO AL-ZARNUJI'S EDUCATIONAL THOUGHT - KHAIRUL NIZAM BIN ZAINAL BADRI (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2022)
Imam Al-Zarnuji's book entitled Ta'lim Al-Muta'allim is no stranger to students in traditional educational institutions. The emphasis on manners and ethics in the process of teaching and learning as found in this book has given a tremendous influence to the residents of the hut in an effort to develop a noble personality. This book is unique because its debate is not only focused on manners and ethics that serve as an interface to the citizens of the traditional school among themselves and the surrounding community; but also covers the philosophy of knowledge that should be studied in its larger theme of discussion. This study seeks to examine the philosophy of knowledge contained in the book that is often studied by the residents of this hut by using a library approach based on qualitative methodology. The results of the study found that Al-Zarnuji’s philosophy of knowledge has the influence of idealism that emphasizes the ability to think and a positive attitude to succeed. In conclusion, idealism has great implications in the field of education as it builds qualities from a spiritual point of view in human beings.